Komunikasi Interpersonal Orang Tua Dalam Memotivasi Anak Sekolah Daring Di Masa Pandemi - Maghfiratull Adawiyah; Iswahyu Pranawukir (Brand Communication, 2022)
As the number of patients infected with COVID-19 spread across the country, President Joko Widodo called on the public to temporarily work, study and worship at home. With the policy to carry out all activities at home during this pandemic, there are things that can be discussed by looking at family interactions as a result of this policy. One of them is that parents finally have to accompany their children to school at home The research problem that the researcher raises is how parental interpersonal communication motivates online school children during the covid-19 pandemic and how the obstacles that occur when motivating online school children. This research is descriptive qualitative with qualitative research theory. The data collection method used is the data collection technique used is Observation, Interview, Documentation and Literacy Review. From the results of research in the field, during the interpersonal communication process in motivating online school children, there are components of effective interpersonal communication including openness, empathy, support, positivity, and equality. In addition, parents also give gifts to their children if their children get good grades. Interpersonal communication barriers that occur when parents motivate their children are situational barriers.